REFLECTION OF MUSIC & DANCE IN ANCIENT INDIAN INSCRIPTION - Sinha, Tanusri (International Journal of Research -GRANTHAALAYAH, 2021)
The word ‘inscription’ is derived from the Latin word ‘Inscripto’ which means something that is inscribed or engraved. It was engraved on clay (terracotta), stone pillars, copper plates, walls of temples, caves, and on the surface of much other metal and also even palm leaves. Very often we’ve seen it on coins and seals. It consists of important texts or symbols that reveal crucial information and evidence of ancient kings and their empires. Music is the soul of Indian culture. Indian music has an affluent tradition with its root in Vedic time. It is said that Indian music owes its origin to the Sāma Veda. The Vedic hymns were chanted with a particular pitch and accent which are used in religious work. Dance in India also has a rich and vital tradition since the beginning of our civilization. Dances of Indi were to give symbolic expressions which are also enlightened to religious ideas. Ancient Inscriptions, Engraving of Inscription, Music, Dance, Epigraphical Evidence.